2018
DOI: 10.1101/445353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Baseline human gut microbiota profile in healthy people and standard reporting template

Abstract: A comprehensive knowledge of the types and ratios of microbes that inhabit the healthy human gut is necessary before any kind of pre-clinical or clinical study can be performed that attempts to alter the microbiome to treat a condition or improve therapy outcome. To address this need we present an innovative scalable comprehensive analysis workflow, a healthy human reference microbiome list and abundance profile (GutFeelingKB), and a novel Fecal Biome Population Report (FecalBiome) with clinical applicability.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Our study does not aim to replicate and validate the findings of such studies, but to show how, if left unaddressed, the differences in sample storage conditions could introduce significant changes in microbial abundance of abundant taxa which are potentially important for our understanding of particular conditions or diseases. The three most-affected bacterial classes in our study, namely Bacteroidia, Clostridia and Bacilli, are among the most dominant microbial classes in the mammalian gut [28][29][30] , therefore it is not surprising to see them strongly affected by technical variations. Both Bacteroidia and Clostridia classes in particular have been found to be significantly impacted by different storage methods in both metagenomic and metaproteomic data 27 .…”
Section: Inconsistent Sample Storage Can Be a Large Source Of Unwanted Variations In Microbiome Studiesmentioning
confidence: 67%
“…Our study does not aim to replicate and validate the findings of such studies, but to show how, if left unaddressed, the differences in sample storage conditions could introduce significant changes in microbial abundance of abundant taxa which are potentially important for our understanding of particular conditions or diseases. The three most-affected bacterial classes in our study, namely Bacteroidia, Clostridia and Bacilli, are among the most dominant microbial classes in the mammalian gut [28][29][30] , therefore it is not surprising to see them strongly affected by technical variations. Both Bacteroidia and Clostridia classes in particular have been found to be significantly impacted by different storage methods in both metagenomic and metaproteomic data 27 .…”
Section: Inconsistent Sample Storage Can Be a Large Source Of Unwanted Variations In Microbiome Studiesmentioning
confidence: 67%
“…In individuals with AD, the count of Ruminococcus callidus is lower. These ndings imply that Ruminococcus callidus could play a protective role in the development and progression of AD through the "gut microbiota abundance-gut-brain" connection [41][42][43] . Recent research has suggested a possible connection between speci c types of Streptococcus, such as Streptococcus pyogenes and Streptococcus suis, and the development of Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 89%
“…In stool, we found that Eubacterium abundance at baseline was positively correlated with the MVA-Nab response. This family of bacteria is known to be associated with gut health (51)(52)(53), and several of its species are higher in centenarians than in either young or elderly adults (54). The potential impact of the gut microbiota on vaccine immunogenicity has been already investigated with systemic vaccines (55) and with oral vaccines including those of rotavirus (RVV), polio, and cholera, mainly in infants/children living in lowincome countries (56,57).…”
Section: Discussionmentioning
confidence: 99%